Determinants of Earnings Quality with Profitability as a Moderating Variable - Dien Sefty Framita; Dian Maulita; Tjut Rana Afra (Institut Agama Islam Negeri Kerinci, 2026)
Purpose: This study aims to empirically examine the influence of company size and capital structure on earnings quality, with profitability serving as a moderating variable, in manufacturing companies listed on the Indonesia Stock Exchange during 2019–2023. Design/Methodology/Approach: The study employs a quantitative research design with a causal-associative approach to test the hypothesized relationships. Data were analyzed using statistical methods to assess the effects of the independent variables—company size and capital structure—on earnings quality, while evaluating the moderating role of profitability. Findings: The empirical results indicate that company size does not significantly affect earnings quality, whereas capital structure has a significant impact. Additionally, profitability does not moderate the relationship between company size and earnings quality but significantly moderates the relationship between capital structure and earnings quality. Research Implications: The findings highlight the importance of capital structure and profitability in managing earnings quality. Companies should carefully consider the composition of debt and equity and how profitability may influence this relationship. While company size does not directly affect earnings quality, firms should remain attentive to size-related factors that could indirectly influence earnings quality outcomes.